Soil Microbial Biomass and Respiration in Afforested Calciorthent - Kumar, Koushlendra; Laik, R.; Das, D.K.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
Soil biological health is an important indicator of soil quality. It is important to evaluate biological indices in afforested soils to understand the soil quality. Microbial biomass carbon (MBC), soil respiration (CO2 efflux), metabolic quotient (q CO2) and microbial quotient (MO) were evaluated in afforested calciorthent after 18 years of plantations by different multipurpose tree species. Significant improvement in soil organic carbon (SOC) of afforested plots over adjacent control plot (without trees) was observed. Terminalia arjuna Bedd., Eucalyptus tereticornis (Smith), and Albizia procera (Roxb.) Benth. were at par with maximum SOC content (7.43-7.54 g kg-1), while Pongamia pinnata (Linn.) Pierrie had lowest value (5.01 g kg-1) among the afforested plots. The role of microbial activity in soil respiration was found to be the highest in the A. procera plot followed by Acacia lenticularis (L.) Willd and the lowest in T. arjuna plot as evidenced by qCO2 value. MO was highest in P.Â pinnata followed by T. arjuna, E. tereticornis and Swietenia mahagoni Linn. plots which had similar values, while A. procera had lowest value. T. arjuna plots had high SOC value with low qCO2 and high microbial quotient values where as A. procera plots, in spite of having high SOC content had high qCO2 and lowest microbial quotient.